Radiometric, Mechanical and Agronomic Characterization of Four Commercial Polymeric Films for Greenhouse Applications - John Eloy Franco; Jesus Antonio Rodríguez-Arroyo; Rafael Jiménez-Lao; Eduardo Garzón; María Teresa Lao (Applied Sciences, 2023)
The objective of this work was the study of four experimental plastic covers (EPCs) to assess the improvement in microclimatic conditions inside a greenhouse. This experiment was based on the comparison of four trilayer plastics: blue, grey, yellow and colorless ECPs. Radiometric and mechanical properties were studied along with the films’ behavior under semi-field conditions through their microclimate parameters. The results show that the addition of the blue pigment causes a considerable reduction in transmission (32.04%) with a reduction in the maximum temperature (+9.8 °C) compared to the other films (14% for grey, 52% for yellow and 46% for colorless). The anti-thermal additive used in the grey EPC did not achieve the desired effect, since it reduced both the photosynthetic active radiation (PAR) (62.33%) and near-infrared radiation (NIR) (62.83%) transmission equally. None of the EPCs achieved a PAR/NIR ratio greater than 1 (0.52 for blue, 0.99 for grey, 0.98 for yellow and 0.99 for colorless). Hindered amine light stabilizers (HALSs) photo-stabilizing additives block UV-A radiation (36.85 for grey) more efficiently compared to nickel quenchers (38.64 for yellow), as they allow earlier PAR transmission. The tensile test showed that all the EPCs manifested a linear relationship between stress and deformation, which defines Young’s modulus.